Berberine in the treatment of type 2 diabetes - literature review - Mazurek, Aleksandra; Pawlicki, Mateusz; Stachyrak, Karol; Mika, Dawid; Mazur, Bartosz; Turek, Kamila; Lambach, Maciej; Greguła, Anna; Kłos, Aleksandra; Wilanowska, Wiktoria (Journal of Education, Health and Sport, 2024)
Introduction and purpose : Type 2 diabetes is currently a serious problem worldwide. Each year, the number of individuals with carbohydrate metabolism disorders is increasing. This is due to an unhealthy lifestyle, lack of physical activity, and a diet rich in highly processed foods. Currently, the treatment of type 2 diabetes is based on the use of oral antidiabetic medications, with the first choice often being a derivative of biguanides, such as metformin. Berberine has been used in China for many years as a hypoglycemic agent, and its efficacy is compared to metformin preparations. This paper focuses on the benefits of using berberine in patients with prediabetes or type 2 diabetes and compares the effects of berberine preparations to classical medications used in diabetes treatment. Material and methods : The literaue was reviewed in PubMed and Google Scholar scientific database in 2013-2023 using the following keywords : berberine, diabetes mellitus type 2, hyperlipidemia, hyperglicemia Conclusions : The studies included in this manuscript have shown that berberine is a promising agent for adjunctive treatment in type 2 diabetes. It exhibits a range of positive effects such as lowering blood glucose levels, improving lipid profile, with no serious adverse effects reported. However, further research is needed to confirm these findings and develop an effective treatment plan.